Immunomodulatory Effects of Azithromycin Revisited: Potential Applications to COVID-19 - Venditto, Vincent J.; Haydar, Dalia; Abdel-Latif, Ahmed; Gensel, John C.; Anstead, Michael I.; Pitts, Michelle G.; Creameans, Jarrod; Kopper, Timothy J.; Peng, Chi; Feola, David J. (Frontiers in Immunology, 2021)
The rapid advancement of the COVID-19 pandemic has prompted an accelerated pursuit to identify effective therapeutics. Stages of the disease course have been defined by viral burden, lung pathology, and progression through phases of the immune response. Immunological factors including inflammatory cell infiltration and cytokine storm have been associated with severe disease and death. Many immunomodulatory therapies for COVID-19 are currently being investigated, and preliminary results support the premise of targeting the immune response. However, because suppressing immune mechanisms could also impact the clearance of the virus in the early stages of infection, therapeutic success is likely to depend on timing with respect to the disease course. Azithromycin is an immunomodulatory drug that has been shown to have antiviral effects and potential benefit in patients with COVID-19. Multiple immunomodulatory effects have been defined for azithromycin which could provide efficacy during the late stages of the disease, including inhibition of pro-inflammatory cytokine production, inhibition of neutrophil influx, induction of regulatory functions of macrophages, and alterations in autophagy. Here we review the published evidence of these mechanisms along with the current clinical use of azithromycin as an immunomodulatory therapeutic. We then discuss the potential impact of azithromycin on the immune response to COVID-19, as well as caution against immunosuppressive and off-target effects including cardiotoxicity in these patients. While azithromycin has the potential to contribute efficacy, its impact on the COVID-19 immune response requires additional characterization so as to better define its role in individualized therapy.